Razrabotka sistemy sorevnovanij s ozdorovitel'noj napravlennosti (na primere boksa) - Aminov, R. C. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The effective solution of many actual problems of the improvement, education and education is impossible without deep understanding of the motivation of a child, without taking into account its propensities, interests and needs. During the participation in competitions the child not only shows the opportunities and skills: here there is also a transition of the process of education into self-education, the development - into self-development.